Association between chronic arsenic exposure and the characteristic features of asthma. (May 2020) - Siddique, Abu Eabrahim; Rahman, Mizanur; Hossain, Md. Imam; Karim, Yeasir; Hasibuzzaman, M.M.; Biswas, Sheta; Islam, Md. Shofikul; Rahman, Atiqur; Hossen, Faruk; Mondal, Victor; Banna, Hasan Ul; Huda, Nazmul; et al.
Abstract: Widespread contamination of arsenic (As) has become a global public health concern. Exposure to As causes respiratory complications. Asthma, a major respiratory complication, is increasing worldwide. However, the effect of chronic As exposure on the risk of asthma remains to be clarified. This study aims to examine the associations between As exposure (water, hair and nail As) and the risk of asthma among 842 individuals exposed to a wide range of As concentrations through drinking water in Bangladesh. Subjects' As exposure levels were measured with ICP-MS. Lung function was examined by a handheld spirometer. Characteristic features of asthma were evaluated by bronchodilator-mediated reversibility in airway obstruction and asthma-like symptoms through a structured questionnaire. Total serum immunoglobulin E (sIgE) levels were measured by immunoassay. As exposure metrics showed inverse associations with lung function measures (FEV1, FEV6, and FEV1/FEV6 ratio) and positive associations with the risks of airway obstruction (AO), reversible airway obstruction (RAO), and asthma-like symptoms. The majority of AO patients (70 of 97) were RAO with one or more characteristic symptoms of asthma. Intriguingly, subjects' As exposure levels showed positive associations with total sIgE levels. Total sIgE in RAO patients was significantly ( p  < 0.001) higher than that in the control group. Thus the results revealed that chronic As exposure was associated with the risk of the characteristic features of asthma. Additionally the association between As exposure and subjects' total sIgE levels and an elevated level of total sIgE in RAO group suggested that As exposure-related asthma might be allergic in nature. Highlights: Chronic arsenic exposure was inversely associated with lung function. Arsenic was positively associated with the risk of reversible airway obstruction. Arsenic exposure was also associated with asthma-like symptoms and serum IgE levels. Serum IgE levels were higher in the subjects with reversible airway obstruction. Arsenic exposure-related asthma may be allergic in nature.